Kualitas Layanan dan Destinasi Wisata terhadap Kepuasan Wisatawan untuk Mengunjungi Kembali Desa Wisata (IPM2KPE, 2022)
This study aims to determine the effect of service quality and destinations on tourist satisfaction to revisit Bongan Tabanan Bali Tourism Village. This research method is descriptive quantitative. This study involved 105 respondents with various characteristics, including gender, age, occupation and income of the respondents. The sampling technique used was purposive sampling, to respondents who had visited at least two times to tourist sites. Data analysis used multiple regression analysis techniques. The results showed that service quality can have a significant positive effect on tourist satisfaction with a value of 0.370 on the indicator of willingness to respond to visitors with the highest value of 0.822. The destination quality variable also has a positive significant effect on tourist satisfaction with a value of 0.206, namely on social attractiveness in Bongan Tabanan Bali Tourism Village with a value of 0.868. Tourist satisfaction variable also has a significant positive effect on return visit interest with a value of 0.354 on the visit indicator in accordance with expectations. In the variable that there is a desire to visit again, there is an indicator with a value that has a positive effect, namely the value of 0.884, which is in the form of intending to travel to Bongan Tabanan Tourism Village, Bali. In conclusion, service quality affects tourist satisfaction which is also influenced by the quality of tourist destinations. The quality of service also has a strong influence on return visits from tourists. Keywords: Tourist Destinations, Service Quality, Return Visits, Tourist Satisfaction